PENGARUH SAAT PEMBERIAN EKSTRAK BAYAM BERDURI (Amaranthus spinosus) DAN TEKI (Cyperus rotundus) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT ( Lycopersicum esculentum) - Kharis Triyono (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRACT Research about the effect of application time of purple nutsedge and spiny amaranth extracts on the growth and yield of tomato was conducted at Mojosongo Surakarta from March until June 2008.Research aimed was to know that the spiny amaranth (Amaranthus spinosus) had the effect as the purple nutsedge (Cyperus rotundus) and are there different of alellophatic activity on either weeds .Polybag experiment conducted in the plastic house,arranged in randomized complete block design [RCBD] with two factors and replicated three times.The first factor was special of weed,consisted of two levels; spiny amaranth and purple nutsedge.the second factor was time application of weed extract, consisted of three lefels; 2,4 and 6 weeks after planting. Result of the analysis showed that spiny amaranth had effect and alellopathic potential as the purple nutsedge. Extract of weed kind and application time of weeds extract did not affected on the growth of tomato. Application time of extract affected on yield of tomato. There were interaction between application time of extract  and kind of weeds. Key words : application time, weed extract , yield of tomato